Computing performability for wireless sensor networks - Herrmann, Johannes U.; Soh, Sieteng; Suresh, R.; Skorjanc, M. (RAMS Consultants, 2012)
The performability of a wireless sensor network (WSN) can be measured using a range of metrics, including reliability (REL) and expected hop count (EHC). EHC assumes each link has a delay value of 1 and devices have no delay or vice versa, which is not necessarily appropriate for WSNs. This paper generalizes the EHC metric into an expected message delay (EMD) that permits arbitrary delay values for both links and devices. Further, it proposes a method based on Augmented Ordered Multivariate Decision Diagram (OMDD-A) that can be used to compute REL, EHC and EMD for WSN with both device and link failures. Simulation results on various networks show the benefits of the OMDD-A approach.